POLA KONSUMSI DAN STATUS NUTRISI PADA REMAJA - K.S, Nirmala; Wulandari, Ratna Feti; Africia, Fresty (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
Various health problems in adolescents are related to meeting balanced nutritional needs. For both boys and girls, nutritional problems that often occur in other teenagers include underweight, overweight/obesity, and anemia. This study identified the food consumption patterns of male and female students and their nutritional status using a cross-sectional design. The sample calculation used total sampling and obtained 33 students. The collection technique is carried out using the convenience method. The instrument used was the Student Consumption Patterns questionnaire and the data was analyzed using chi-square. The research results showed that 57.6% had poor consumption patterns. A nutritional monitoring program for adolescents is needed which includes maintaining nutritional status, consumption patterns and risk factors related to nutrition. Persuasive health education is needed by utilizing electronic media which is currently widely accessed, especially by teenagers.